PENDIDIKAN BERORIENTASI PROFESI DALAM EKONOMI GLOBAL - Suripto Suripto (Fakultas Ekonomi Universitas Negeri Jakarta, 2010)
ABSTRACTIn challenging global economic increasingly sharply, readiness of alteration of labour patterned thinking in position and behavior of claiming readiness of technical interest, fasility process and cooperation in team. In job activity beside hard skills also soft skill; hard skills in general has been assumed fullfills; but which still needing is soft skills. Strives to give interest stock soft skills becomes attention which is enough serious to teaching about character building and leadership in the form of practical that is through atmosphere academic created to support soft skills. Keywords: Profession Education, Global Economic.